2005
DOI: 10.1016/j.cardiores.2005.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of NAD(P)H oxidase in the regulation of cardiac L-type Ca channel function during acute hypoxia

Abstract: Objective: The role of NAD(P)H oxidase in regulating cellular production of reactive oxygen species (ROS) and the L-type Ca 2+ channel during acute hypoxia was examined in adult ventricular myocytes from guinea pig. Methods: The fluorescent indicator dihydroethidium (DHE) was used to detect superoxide and the response of the L-type Ca 2+ channel to hadrenergic receptor stimulation was used as a functional reporter since hypoxia increases the sensitivity of the L-type Ca 2+ channel (I Ca-L ) to isoproterenol (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 44 publications
1
50
0
1
Order By: Relevance
“…10,16 Generation of superoxide was assessed in 24-hour guinea pig myocytes or 36-hour contracting neonatal myocytes using the fluorescent indicator dihydroethidium (DHE) (5 mol/L, 515-to 560-nm excitation filter, 590 long pass emission; Molecular Probes), as previously described. 17 Application of the superoxide scavengers N-tert-butyl-␣-phenyl-nitrone and superoxide dismutase significantly decreased DHE signal, confirming specificity of the indicator for superoxide (nϭ4). 17 Comparisons using inhibitors were made with cells exposed to 30 mol/L H 2 O 2 for 5 minutes followed by 10 U/mL catalase for 5 minutes and were performed on the same day.…”
Section: Detection Of Superoxidementioning
confidence: 85%
“…10,16 Generation of superoxide was assessed in 24-hour guinea pig myocytes or 36-hour contracting neonatal myocytes using the fluorescent indicator dihydroethidium (DHE) (5 mol/L, 515-to 560-nm excitation filter, 590 long pass emission; Molecular Probes), as previously described. 17 Application of the superoxide scavengers N-tert-butyl-␣-phenyl-nitrone and superoxide dismutase significantly decreased DHE signal, confirming specificity of the indicator for superoxide (nϭ4). 17 Comparisons using inhibitors were made with cells exposed to 30 mol/L H 2 O 2 for 5 minutes followed by 10 U/mL catalase for 5 minutes and were performed on the same day.…”
Section: Detection Of Superoxidementioning
confidence: 85%
“…ROS generation was determined using the oxidant-sensitive fluorogenic probe DHE (excitation wavelength, 488 nm; emission wavelength, 610 nm) essentially as described elsewhere (Hool et al, 2005). In brief, primary cultured cardiomyocytes were loaded with 100 nM DHE for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Wright et al [92] showed that prolyl hydroxylation is the oxygen-sensing mechanism in cardiac myocytes, which in turn regulates HIF-1, heme oxygenase-1, and GLUT1. While the role of NADPH oxidase in O 2 sensing in cardiac myocytes has not been reported, this enzyme has been shown to be expressed and play a role in the development of cardiac hypertrophy and in the transition to heart failure [93][94][95][96][97][98][99][100]. The concept that the heart directly senses changes in oxygen tension has recently been supported by results from our laboratory that 20 min of intermittent hypoxia can elicit significant changes in gene expression and protein modifications in mouse hearts [101].…”
Section: Oxidative Stress In Animal Models Of Intermittent Hypoxiamentioning
confidence: 99%